Category of the Common Good from the COVID-19 Pandemic Perspective - Gorynia Marian; Słodowa-Hełpa Małgorzata (Studies in Logic, Grammar and Rhetoric, 2022)
In this study, edited on the basis of a critical review of domestic and foreign literature, as well as authors’ own analyzes, previously presented in several articles (Słodowa-Hełpa 2015; Gorynia 2021 and 2022), mainly in two shorter texts published in popular magazines with a range of Poland (Gory-nia and Słodowa-Hełpa 2022a, 2022b), selected aspects of the concept of the common good from the perspective of the Covid-19 pandemic were presented.